2018
DOI: 10.1042/bsr20171454
|View full text |Cite|
|
Sign up to set email alerts
|

Resveratrol attenuates high glucose-induced nucleus pulposus cell apoptosis and senescence through activating the ROS-mediated PI3K/Akt pathway

Abstract: Background: Diabetes mellitus is closely correlated with disc degeneration. Nucleus pulposus (NP) cell apoptosis and senescence are typical cellular features within the degenerative disc. Resveratrol is a newly identified phytoalexin that has protective effects on cartilaginous tissue.Objective: To investigate the whether resveratrol can protect against high glucose-induced NP cell apoptosis and senescence, and the potential mechanism in this process.Methods: Rat NP cells were cultured in either 10% FBS cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 38 publications
4
72
0
1
Order By: Relevance
“…There are two types of DM (type 1 DM and type 2 DM) with approximately 90% of DM patients are type 2 DM [1]. Accumulating evidence has shown that DM is a crucial effecter in the progression of intervertebral disc degeneration [2][3][4][5][6]. The morbidity of disc degeneration is much higher in DM patients than that in non-DM patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of DM (type 1 DM and type 2 DM) with approximately 90% of DM patients are type 2 DM [1]. Accumulating evidence has shown that DM is a crucial effecter in the progression of intervertebral disc degeneration [2][3][4][5][6]. The morbidity of disc degeneration is much higher in DM patients than that in non-DM patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, High glucose treated MSC exhibited significantly decreased cell migration, increased cell senescence and higher intracellular reactive oxygen species . However, reduction in glucose concentration could led to decreased cell apoptosis and increased proliferation rate of MSC …”
Section: Introductionmentioning
confidence: 95%
“…For example, sirt6 has shown potent anti-senescent and anti-apoptotic properties in models of age-related degenerative disease (6). Furthermore, overproduction of reactive oxygen species (ROS) has been reported to be involved in the senescence and apoptosis of NP cells and may accelerate the degenerative process (7). Previous studies also demonstrated that tumor necrosis factor-α promotes changes in the production of extracellular matrix (EcM) molecules, tissue degradation (8) and premature senescence of NP cells (9,10).…”
Section: Introductionmentioning
confidence: 99%